Perspectives: Mental health challenges and medical trauma: focus on cystinosis patients and caregivers - Doyle, Maya H.; Meschke, Chelsea (Frontiers in Pediatrics, 2025)
As the lifespan of cystinosis patients extends, mental health issues increasingly impact both patients and their caregivers. The emotional journey for patients and “raregivers” has been mapped, providing a valuable guide across a patient's lifetime. Common mental health challenges within the cystinosis community include anxiety, depression, PTSD, grief/loss, bullying, peer challenges, body image issues, and underappreciation of gender and sexual identity, alongside co-occurring mental health diagnoses. A literature review was conducted and a first presentation given on this under-appreciated topic at the New York Academy of Medicine in May 2024. Pediatric Medical Trauma is documented in the literature; however, post-traumatic stress disorder (PTSD) related to medical trauma and caregiving across the lifespan for both patients and carers is often subsumed under general stress, leading to a lack of targeted interventions. Medical events, from ICU experiences to routine blood draws, can be traumatic or trigger past trauma, resulting in classic PTSD symptoms. Despite referrals for mental health services, there is often a lack of awareness about specific interventions for post-traumatic stress, such as TF-CBT, DBT, EMDR, ACT, and other forms of mindfulness-based stress reduction. Healthcare teams are encouraged to monitor for signs of mental health distress, including reduced adherence and changes in appearance, affect, and demeanor towards care. Proactive conversations and anticipatory guidance are essential to educate and normalize mental health care needs. Ensuring patients and families are aware of available resources through disease-specific organizations, hospital services, and local mental health agencies is vital.